Kaidah Fiqhiyyah dan Aplikasinya dalam Hukum Keluarga Tentang Radha’ah (Menyusui) - Heriandi; Muhammad Amar Adly; Heri Firmansyah; Rahmad Hidayat (Yayasan Dar Arrisyah Indonesia, 2025)
This study investigates the Islamic legal principles governing radha’ah (breastfeeding) and its implications in family law, particularly in defining mahram (non-marriageable kinship) relationships. Rooted in classical and contemporary Islamic jurisprudence, this qualitative, library-based research identifies the foundational legal maxims: “What is prohibited by lineage is also prohibited by breastfeeding,” “The husband’s milk is the cause of prohibition,” and “Nutrition is the legal cause (‘illah) of prohibition in breastfeeding.” The study emphasizes that radha’ah establishes a familial bond equivalent to nasab (bloodline) and is effective when a child under two years of age is breastfed at least five times. Using sources such as the Qur’an, Prophetic traditions, juristic consensus (ijma’), and classical texts from various madhahib (schools of thought), the research reveals that both the breastfeeding woman and her husband (as the source of the milk) establish mahram ties with the breastfed child. Furthermore, it underscores the biological basis of Islamic rulings by demonstrating that nutritional transmission through milk forms the basis for legal prohibition, reflecting the maqāṣid al-sharī‘ah (objectives of Islamic law). This work offers vital insight into the intersection of biological function, legal normativity, and socio-religious ethics in Islamic family jurisprudence.